Continued existence of cows disproves central tenets of capitalism? - Santosh Anagol; Alvin Etang; Dean Karlan (Yale University, Economic Growth Center, 2013)
We examine the returns from owning cows and buffaloes in rural India. We estimate that when valuing labor at market wages, households earn large, negative average returns from holding cows and buffaloes, at negative 64% and negative 39% respectively. This puzzle is mostly explained if we value the household's own labor at zero (a stark assumption), in which case estimated average returns for cows is negative 6% and positive 13% for buffaloes. Why do households continue to invest in livestock if economic returns are negative, or are these estimates wrong? We discuss potential explanations, including labor market failures, for why livestock investments may persist.
Keywords: E21; M4; Q1; O12; 330; Investment; Profits; Livestock; Labor markets; Tierhaltung; Ländlicher Raum; Rendite; Lohn; Haushaltsökonomik; Indien